Understanding Scope and Challenges of Adoption & Implementation of Artificial Intelligence in the Indian Small and Medium-Scale Textile Industry - Kumar, Pawan (Global journal of Business and Integral Security, 2025)
This research investigates how small and medium-sized enterprises (SMEs) in India’s textile sector, which is vital to the country’s economy, are implementing and utilising artificial intelligence (AI). AI has the potential to significantly increase productivity and competitiveness in this industry. Numerous textile SMEs have been hesitant to embrace AI owing to obstacles including a lack of awareness regarding its advantages, apprehensions about expenses, technological intricacies, and inadequate technical expertise. This research seeks to evaluate the present status of AI implementation in Indian textile SMEs, identify the principal factors affecting AI utilisation, and comprehend the challenges encountered by these enterprises. By combining both data analysis and real-world insights, the study offers practical recommendations to policymakers, industry leaders, and researchers for developing strategies that support AI integration in this sector. Recent data indicate that the textile industry employs around 45 million individuals countrywide, including 3.52 million handloom workers, highlighting its importance to India. During the fiscal year 2018-19, textiles accounted for 7% of India’s industrial output by value. The sector has garnered substantial investments, particularly in coloured and printed textiles. From March 2000 to April 2021, the sector attracted Foreign Direct Investment (FDI) amounting to USD 3.75 billion. These statistics emphasise the textile and clothing sector’s vital contribution to employment generation, economic expansion, and investment attraction. Incorporating AI into this sector can create more potential for innovation and advancement, helping both the textile industry and the Indian economy overall.